Revolusi Industri 4.0 dan Pengaruhnya pada Kenakalan Remaja - Jamilah Jamilah; Choli Astutik; Khoirul Asiah (STKIP PGRI SUMENEP, 2020)
The 4.0 revolution era which belongs to digital and internet nowadays has been extremely dominated by teenagers. This has huge impact on various aspects, especially in terms of biological, psychological, social, and spiritual. Adolescence is a time for a transition from childhood to be an adult human. In this era, there are many both behavioral changes and developments that occur in each individual. This paper will try to describe and analyze the industrial revolution 4.0 and juvenile delinquency with a strength-based approach on their adolescent life. The Teenagers nowadays are tend to influenced by the social media environment in establishing their self-concept. It includes the identity search for youth through social media. The netizen’s Positive reactions will strengthen and support the identity of teenagers. On the other hands, netizen's negative reactions will be affected to the identity confusion among teenagers.